Host-Pathogen Interactions Made Transparent with the Zebrafish Model - Meijer, Annemarie H (Bentham Science Publishers Ltd, 2011)
The zebrafish holds much promise as a high-throughput drug screening model for immune-related diseases, including inflammatory and infectious diseases and cancer. This is due to the excellent possibilities for in vivo imaging in combination with advanced tools for genomic and large scale mutant analysis. The context of the embryo’s developing immune system makes it possible to study the contribution of different immune cell types to disease progression. Furthermore, due to the temporal separation of innate immunity from adaptive responses, zebrafish embryos and larvae are particularly useful for dissecting the innate host factors involved in pathology. Recent studies have underscored the remarkable similarity of the zebrafish and human immune systems, which is important for biomedical applications. This review is focused on the use of zebrafish as a model for infectious diseases, with emphasis on bacterial pathogens. Following a brief overview of the zebrafish immune system and the tools and methods used to study host-pathogen interactions in zebrafish, we discuss the current knowledge on receptors and downstream signaling components that are involved in the zebrafish embryo’s innate immune response. We summarize recent insights gained from the use of bacterial infection models, particularly the Mycobacterium marinum model, that illustrate the potential of the zebrafish model for high-throughput antimicrobial drug screening.